Ozone patterns in Maceió: Insights into seasonal and geographic varibility - Amaury de Souza; Celina M. Takemura; Deniz Özonur; Elias Silva de Medeiros; Ivana Pobocikova; Janice F. Leivas; José Francisco de Oliveira-Júnior; Kelvy Rosalvo Alencar Cardoso; Marcel Carvalho Abreu; Wagner Alessandro Pansera; Jose Roberto Zenteno Jimenez; Sneha Gautam (Geosystems and Geoenvironment)
This study analyzes the Total Ozone Column (TCO) over six cities in Alagoas, Brazil, aiming to evaluate their spatial and temporal homogeneity and identify seasonal and annual patterns from 2008 to 2016. TCO is a key indicator for monitoring the ozone layer and its implications for public health, given ozone's role in filtering ultraviolet radiation. The analysis utilized satellite-derived TCO data, with variance homogeneity assessed using the Bartlett test at a 95% significance level. Descriptive statistical analyses characterized the temporal distribution of TCO values, and probability density functions (PDFs) identified the best-fitting statistical distribution.The findings indicate significant homogeneity in annual and seasonal TCO concentrations, with an annual mean of 263.24 ± 9.91 DU. A biannual TCO cycle was observed, with peaks in spring and lows in fall, influenced by Earth's orbit and ozone photochemistry. The data were best represented by a normal distribution, reflecting the role of the Brewer-Dobson Circulation in maintaining ozone uniformity and mitigating disruptions from phenomena like the Antarctic Polar Vortex.These results emphasize the need for continuous monitoring of ozone variability, as fluctuations in TCO can affect ultraviolet radiation levels and, consequently, public health outcomes such as skin cancer and ocular diseases. The study underscores the importance of integrating TCO data into environmental policies and public health strategies, particularly in regions with high solar radiation exposure. The study's limited statistical sensitivity and geographic coverage highlight the necessity of further research on factors influencing ozone distribution and its broader environmental and health implications.